The problem of harm in world politics : theoretical investigations - Linklater, Andrew (Cambridge ;New York : Cambridge University Press, 2011)
"The need to control violent and non-violent harm has been central to human existence since societies first emerged. This book analyses the problem of harm in world politics which stems from the fact that societies require the power to harm in order to de
The concept of harm -- The harm principle and global ethics -- Harm and international relations theory -- The sociology of civilizing processes -- Historical sociology and world politics: structu.
Index.
Includes bibliographical references (p. 267-298).
Keywords: International relations -- Moral and ethical aspects; Uluslararası İlişkiler -- Felsefe; Uluslararası ilişkiler -- Psikolojik yönler; Harm reduction -- Political aspects; Uluslararası ilişkiler -- Ahlak ve etik yönleri